2018
DOI: 10.1111/bju.14513
|View full text |Cite
|
Sign up to set email alerts
|

Four‐year outcomes from a multiparametric magnetic resonance imaging (MRI)‐based active surveillance programme: PSA dynamics and serial MRI scans allow omission of protocol biopsies

Abstract: Men with low-risk Gleason 3 + 3 prostate cancer on active surveillance can forgo protocol biopsies in favour of MRI and PSA monitoring with selective re-biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 25 publications
8
31
0
1
Order By: Relevance
“…Some authors report treatment rates as low as 11.7%, with the majority of men treated at a yearly rate of <4% after the first 2 yr (with a median follow-up of 39 mo) [18] . We showed that Gleason grade and MRI visibility at baseline are associated with EFS and treatment-free survival, a finding previously confirmed by others [17] . We also believe that WW after AS should not necessarily be viewed as a “failure”, but often as a “graduation” event.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Some authors report treatment rates as low as 11.7%, with the majority of men treated at a yearly rate of <4% after the first 2 yr (with a median follow-up of 39 mo) [18] . We showed that Gleason grade and MRI visibility at baseline are associated with EFS and treatment-free survival, a finding previously confirmed by others [17] . We also believe that WW after AS should not necessarily be viewed as a “failure”, but often as a “graduation” event.…”
Section: Discussionsupporting
confidence: 88%
“…In other AS studies, 5-yr conversion rates are even higher [15] . By comparison, small imaging-based studies have reported active treatment rates of 27.5% (with median time to treatment 4.2 yr) and 30% (with median time to treatment 1.55 yr) [16] , [17] . Some authors report treatment rates as low as 11.7%, with the majority of men treated at a yearly rate of <4% after the first 2 yr (with a median follow-up of 39 mo) [18] .…”
Section: Discussionmentioning
confidence: 96%
“…This study supports a growing body of evidence that mpMRI may be adopted as the primary surveillance tool for men on AS. The finding regarding PSA velocity should be interpreted carefully as it contrasts with previous studies, which found that PSA dynamics have a limited role as independent predictors of disease progressions in AS .…”
supporting
confidence: 85%
“…In this issue of the BJUI , Gallagher et al. report the outcomes of an AS programme using selective repeat biopsy based on multiparametric MRI (mpMRI) and PSA dynamics. The authors address the important issue of whether mpMRI can be used to safely avoid repeat biopsies in AS protocols.…”
mentioning
confidence: 99%
See 1 more Smart Citation